Real-time electrochemical recording of dopamine release under optogenetic stimulation. - Wen-Tai Chiu; Che-Ming Lin; Tien-Chun Tsai; Chun-Wei Wu; Ching-Lin Tsai; Sheng-Hsiang Lin; Jia-Jin Jason Chen (PLoS ONE, 2014)
Dopaminergic PC12 cells can synthesize and release dopamine, providing a good cellular model for investigating dopamine regulation. Optogenetic stimulation of channelrhodopsin-2 provides high spatial and temporal precision for selective stimulation as a powerful neuromodulation tool for neuroscience studies. The aim of this study is to measure dopamine release from dopaminergic PC12 cells under optogenetic stimulation using electrochemical recording of self-assembled monolayers modified microelectrode with amperometric measurement in real time. The activation of PC12 cells under various optogenetic stimulation schemes are characterized by measuring single-cell Ca(2+) imaging. After 10 seconds of optogenetic stimulation, the evoked intracellular Ca(2+) level and dopamine current of channelrhodopsin-2-transfected PC12 cells were 1.6- and 3.5-fold higher than those of the control cells. The optogenetic stimulation effects on Ca(2+) influx and dopamine release were 81% and 63% inhibition by using a Ca(2+) channel antagonist Nifedipine. The results indicate that optogenetic stimulation can evoke voltage-gated Ca(2+) channel-dependent dopamine exocytosis from PC12 cells in a cell specific, temporally precise and dose-dependent manner. This proposed dopamine recording system can be developed to be a good cell model for dopamine regulation and drug screening in vitro, or dopaminergic cell implantation therapy in vivo using optogenetic stimulation in a precise and convenient way.